Unwanted Pregnancy and Its Risk Factors Among Pregnant Women in Tehran, Iran - Nourollahpour Shiadeh; Kariman; Bakhtiari; Mansouri; Mehravar (Kashan University of Medical Sciences, 2016)
Background Unwanted pregnancies remain a main public health problem worldwide. In Iran, comparative studies on the risk factors of unwanted pregnancies and their effects on maternal health are rare. Objectives This study was conducted to determine the risk factors of unwanted pregnancies and their impact on maternal behavior during pregnancy. Patients and Methods This case-control study was carried out on 240 pregnant women who referred to the healthcare centers of Shahid Beheshti University of Medical Science for receiving routine prenatal care. Of the 240 women, 120 had unwanted pregnancies (case) and 120 had wanted pregnancies (control). Data collection was performed using a researcher-made questionnaire. The data were analyzed using chi-square tests, Fisher's exact tests, t-tests, Mann Whitney U tests, odds ratios, and logistic regression analysis. Results Compared to women with wanted pregnancies, those with unwanted pregnancies were more employed (23.3% vs. 12.5%, P = 0.006), had lower education levels (P = 0.016), had lower incomes (P = 0.009), had more children (1.30 ± 1.08 vs. 0.53 ± 0.67, P = 0.001), and had more traditional marriages (15% vs. 3.3%, P = 0.002). Also, women with unwanted pregnancies had significantly lower tendencies to do prenatal care (P = 0.002), had a higher tendency to abortion (P = 0.001), had higher previous abortion attempts (P = 0.001), and had higher levels of unhealthy behaviors (P = 0.017) compared to those with wanted pregnancies. Conclusions Lower education and socioeconomic status, longer marriage duration, being employed, and unwilling of spouse were among the risk factors of unwanted pregnancies. These women are at high risk for unhealthy behaviors and have a higher tendency to abortion that consequently threatens their health.